Methods for the formation of professionally-based competence using digital technologies (Journal of Educational Sciences, 2023)
This scientific article is dedicated to the study and development of methods for the formation ofprofessionally-based competence using digital technologies. The purpose of this article is to developmethods for the formation of professionally-based competence of future foreign language teachers usingdigital technologies and to verify its effectiveness. The scientific and practical significance of thescientific article is that the results of the study can be used in the practical work of the university andschool teachers, in the system of training and refreshment training of teaching staff. Theoretical andempirical methods were used to achieve the purpose of the scientific article. An analysis of local and foreignliterature on the research topic was conducted. Methods for the formation of professionally-basedcompetence using digital technologies were developed and their effectiveness was tested. 106 studentsof the Ilyas Zhansugurov Zhetysu University took part in the experimental work. The results of thescientific article reveal that professionally-based competence is successfully formed through using thedeveloped methods of using digital technologies. The value of the study is that the developed methodsfor the formation of professionally-based competence using digital technologies can be used in teachingprofessionally-based disciplines. The practical significance of the results of a scientific article is reflectedin the use of research results in universities and the professional training of specialists.Key words: professional competence, professionally-based competence, digital technologies, digitaleducational platforms, digital content.